ANALISIS KELAYAKAN USAHA PENANGKAPAN IKAN PADA MUSIM PERALIHAN OLEH NELAYAN DI KAMPUNG ONGGAYA DISTRIK NAUKENJERAI KABUPATEN MERAUKE - Yunus Paskalis Imbanop; Maria Maghdalena Diana Widiastuti; Riza Fachriza (Musamus Journal of Agribusiness, 2019)
This study aims to determine and analyze the income and feasibility of fishing businesses. The study was conducted in Onggaya Village, Naukenjerai District, Merauke Regency, for 3 (three) months from March to May 2018. The population in this study were fishermen who worked fishing business regularly and have been operating for more than 5 years. Sampling was done randomly, while the data analysis used revenue cost ratio (R/C). This technique is used to analyze the costs, benefits, and feasibility of fishing businesses. The results showed that the average total income was Rp. 164,000 per day and the average total cost was Rp. 151,782 per day. Total average profit obtained is Rp. 12,218 per day with R/C ratio of fishing business was 1,08. This ratio has met the standards of business feasibility because R / C ratio>1, means that every Rp. 1 cost will provide revenue 1.08 times. Keywords: Feasibility analysis, Onggaya village fishing